ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA PADA PT. MANDOM INDONESIA TBK PERIODE 2018-2022 - Arifman Ndruru (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The aim of this research is to determine the efficiency of using working capital at PT. Mandom Indonesia, Tbk for the period 2018 to 2022. This research is a qualitative research. To analyze the efficiency of PT. Mandom Indonesia, Tbk use of working capital, namely by the liquidity ratio namely the current ratio, activity ratio namely the working capital turnover ratio, and the profitability ratio namely NPM, using financial data from PT. Mandom Indonesia, Tbk for the period 2018-2022 which can be accesed via the website www.idx.co.id. Bassed on the results of the analysis carried out, the calculation of the company’s current ratio from 2018-2022 is an average of 2 times or more >2 times, meaning the company is efficient or able to pay its obligations,the average calculation of the company’s working capital turnover ratio from 2018-2022 is below 6 times (<6 ), meaning that working capital turnover is imefficient, the company’s NPM gain from 2018-2022 is on average below 20%, meaning the company is no efficient generating net profit.